Insight into the mechanism of AML del(9q) progression: hnRNP K targets the myeloid master regulators CEBPA (C/EBPα) and SPI1 (PU.1) - Rahn, Kerstin; Abdallah, Ali T.; Gan, Lin; Herbrich, Shelley; Sonntag, Roland; Benitez, Oscar; Malaney, Prerna; Zhang, Xiaorui; Rodriguez, Ashely G.; Brottem, Jared; Marx, Gernot; Bruemmendorf, Tim H.; et al. (Biochimica et biophysica acta. Gene regulatory mechanisms, 2024)
Deletions on the long arm of chromosome 9 (del(9q)) are recurrent abnormalities in about 2 % of acute myeloid leukemia cases, which usually involve HNRNPK and are frequently associated with other known aberrations. Based on an Hnrnpk haploinsufficient mouse model, a recent study demonstrated a function of hnRNP K in pathogenesis of myeloid malignancies via the regulation of cellular proliferation and myeloid differentiation programs. Here, we provide evidence that reduced hnRNP K expression results in the dysregulated expression of C/EBP alpha and additional transcription factors. CyTOF analysis revealed monocytic skewing with increased levels of mature myeloid cells. To explore the role of hnRNP K during normal and pathological myeloid differentiation in humans, we characterized hnRNP K-interacting RNAs in human AML cell lines. Notably, RNA-sequencing revealed several mRNAs encoding key transcription factors involved in the regulation of myeloid differentiation as targets of hnRNP K. We showed that specific sequence motifs confer the interaction of SPI1 and CEBPA 5 ' and 3 ' UTRs with hnRNP K. The siRNA mediated reduction of hnRNP K in human AML cells resulted in an increase of PU.1 and C/EBP alpha that is most pronounced for the p30 isoform. The combinatorial treatment with the inducer of myeloid differentiation valproic acid resulted in increased C/EBP alpha expression and myeloid differentiation. Together, our results indicate that hnRNP K post-transcriptionally regulates the expression of myeloid master transcription factors. These novel findings can inaugurate novel options for targeted treatment of AML del (9q) by modulation of hnRNP K function.
Gesehen am 27.11.2024